Análisis de la aplicación de la NIC 41 en los activos biológicos de las plantaciones de banano. - Jaramillo Verdugo, Digna Isabel; Bastidas Real, Melissa Victoria (Machala : Universidad Técnica de Machala, 2022)
The International Accounting Standard (IAS 41) is in charge of determining the accounting treatment, the presentation of the financial statements and the information to be disclosed of the agricultural companies, of the biological assets of the entity from its growth, degradation, production and procreation, as well as the initial assessment of production up to the point of harvest or collection. Therefore, for this research, an analysis of the application of this standard was carried out in the biological assets of banana plantations, in order to identify the accounting accounts involved. By applying the quantitative method with which the investigation will be carried out and taking as a reference financial statements of agricultural and banana exporting companies in the city of Machala, information that was obtained from the Superintendency of Companies, leaving as a result that a large part of the companies does not apply the regulation for the accounting treatment of their biological assets. Therefore, it was concluded that most of these companies do not apply this regulation due to the difficulty at the time of making the application, because they consider that it is presented in a very general way, since it is difficult for them to obtain all the information. necessary for the preparation of the financial statements.
La Norma Internacional de Contabilidad (NIC 41), es la encargada de determinar el tratamiento contable, la presentación de los estados financieros y la información a revelar de las empresas agrícolas, de los activos biológicos de la entidad desde su crecimiento, degradación, producción y procreación, así como la valoración inicial de la producción hasta el punto de cosecha o recolección. Por ello, para esta investigación se llevó a cabo el análisis de la aplicación de esta norma en los activos biológicos de las plantaciones de banano, con el fin de identificar las cuentas contables que intervienen. Mediante la aplicación del método cuantitativo con el cual se llevará a cabo la investigación y tomado como referencia estados financieros de empresas agricultoras y exportadoras de banano de la ciudad de Machala, información que se obtuvo de la Superintendencia de Compañías, dejando como resultado que gran parte de las empresas no aplican la normativa NIC 41 para el tratamiento contable de sus activos biológicos. Por lo que, se llegó a la conclusión que la mayoría de estas empresas no aplican esta normativa debido a la dificultad al momento de realizar la aplicación, porque consideran que se presenta de forma muy general, ya que, les resulta difícil obtener toda la información necesaria para la realización de los estados financieros.
Keywords: NIC 41; ACTIVOS BIOLOGICOS; PLANTACIONES DE BANANO